Developing “REPROKOPIKREATIF” model to enhance collaborative skills and creative thinking of junior high school students in natural science-biology learning - Sri Wahyuni; Iin Hindun; N. Nurwidodo (JPBI (Jurnal Pendidikan Biologi Indonesia))
The 21st-century competencies—particularly creative thinking and collaborative skills—among junior high school students in Indonesia was underdevelopment. Science-Biology learning is still dominated by conventional, teacher-centered methods that limit student engagement and higher-order thinking. Although the Kurikulum Merdeka promotes the use of Project-Based Learning (PjBL), many teachers lack sufficient training and face challenges in aligning learning objectives with real-world contexts. These obstacles result in students showing fair to below-average levels in collaboration and creativity. To address this gap, this study aims to develop and validate the “REPROKOPIKREATIF” model to enhance collaborative skills and creative thinking in Natural Science-Biology education through a structured PjBL approach. Grounded in the ADDIE framework, the model focuses on improving the planning stage of PjBL by offering systematic procedures for formulating essential questions and designing project plans. It integrates concept maps, group heterogeneity, and scaffolding strategies as practical tools for teachers and learners. The implementation results demonstrate high model validity, improved teacher performance, and increased student engagement. Quantitative data from pretest and posttest comparisons show significant gains in students’ creative dimensions—fluency, originality, elaboration—and collaborative aspects like respect and responsibility. The REPROKOPIKREATIF model provides a validated, practical solution to strengthen key competencies in line with Kurikulum Merdeka.